Improvement of COVID‐19 with renal failure and paralytic ileus by using steroids. Issue 1 (29th November 2020) - Kitamura, Atsushi; So, Clara; Jinta, Torahiko
Abstract: A 51‐year‐old man attended our hospital with chief complaints of fever and diarrhoea for the past eight days. Chest computed tomography showed peripherally dominant ground‐glass opacity. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA was detected by real‐time polymerase chain reaction, and the patient was diagnosed with coronavirus disease (COVID‐19). His clinical course included respiratory failure, acute kidney injury, and paralytic ileus. Systemic management was difficult, but he recovered with high‐dose steroids, temporary haemodialysis therapy, and a nasointestinal tube, without antiviral drugs. COVID‐19 can be associated with multiple organ failure due to vascular endothelial injury. Abstract : Coronavirus disease (COVID‐19) may be associated with multiple organ failure due to vascular endothelial damage. Here, we report a case of COVID‐19 in which a patient suffered from ileus complications and was difficult to manage systemically. However, he recovered with high doses of steroids, hemodialysis, and the nasal intestine without the use of antivirals.